Effects of glycine propionyl-L-carnitine supplementation on anaerobic work capacity and lactate accumulation are dosage dependent - Jacobs, P.; Goldstein, E. R.; Blackburn, W.; Orem, I.; Hughes, J. (The Journal of Strength and Conditioning Research, 2010)
Background: It has been demonstrated that short term administration of glycine propionyl-L-carnitine (GPLC) produces significantly elevated levels of nitric oxide metabolites at rest and in response to reactive hyperaemia. It has been recently shown that acute GPLC supplementation also produces enhanced anaerobic work capacity with reduced lactate production in resistance trained males. However, it is not known what effects chronic GPLC supplementation has on anaerobic performances or on lactate clearance. The purpose of this study was to examine the effects of varied dosages of chronic GPLC supplementation on the performance of repeated high intensity stationary cycle sprints with limited recovery periods in resistance trained male subjects. Forty-five male resistance trained subjects participated in a double-blind, placebo-controlled, cross-over design study. All subjects had completed two testing sessions, one week between, 90 minutes following oral ingestion of either 4.5 grams GPLC or 4.5 grams cellulose (PL), in randomized order. The exercise testing protocol consisted of five 10-second Wingate cycle sprints separated by 1-minute active recovery periods. Following completion of the second test session, the 45 subjects were randomly assigned to receive either 1.5g, 3.0g, or 4.5g GPLC per day for a 28 day period. During the one month supplementation period, subjects were directed to continue with their own individual training and nutritional programs. Subjects completed a third test session following the 29 d of GPLC supplementation using the same testing protocol and the respective dosage on the day of testing. Peak (PP) and mean values (MP) of sprint power output and percent decrement of power (DEC) were determined per bout and standardized relative to body mass. Heart rate (HR) and blood lactate (LAC) were measured prior to, during and following the five sprint bouts. Analyses indicated significant time X group interactions for PP, MP, DEC, and LAC. Secondary analyses showed that sprint bouts three, four and five produced 2 - 5% lower values of PP and 3 - 7% lower values of MP with GPLC 3.0 or 4.5g per day than baseline PL values. Conversely, 1.5g GPLC produced 3 - 6% higher values of PP and 2 -5% higher values of MP compared with PL baseline values. DEC values were 11-15% greater across the five sprint bouts with 4.5g GPLC, 8 - 16% higher with 3.0g GPLC, but the 1.5g GPLC supplementation produced DEC values -5%, -3%, + 4%, + 5%, and + 2% different from the baseline PL values. LAC values were significantly different (p <0.05) only 14min following sprints in the 1.5g GPLC supplementation group. The effects of GPLC supplementation on anaerobic work capacity and lactate accumulation appear to be dosage dependent. Four weeks of GPLC supplementation at 3.0 and 4.5 g per day resulted in reduced power output and increased rate of power decrement compared with values derived from baseline placebo testing. Supplementation of 1.5 g per day of GPLC produced enhanced values of PP and MP with significantly reduced lactate accumulation as previously reported with an initial acute 4.5 dosage. GPLC appears to be a useful dietary supplement to enhance anaerobic work capacity and presumably sport performance, but the dosage must be specifically applied relative to the work challenges.